Fat body, hemolymph and ovary routes for delivery of substances to ovary in Melipona quadrifasciata anthidioides: Differences among castes through the use of electron-opaque tracers - Da Cruz-Landim, Carminda [UNESP]; Roat, Thaisa Cristina [UNESP]; Berger, Bruno [UNESP] (Oxford University Press (OUP), 2013)
The yolk protein precursor, vitellogenin (Vg), in bees is synthesized in the fat body trophocytes, delivered to the hemolymph and ultimately absorbed from there during the vitellogenic phase of oocytes in the active ovary. The routes tracing the material exchange that occurs between the trophocytes and the hemolymph, in addition to the transportation from the hemolymph to the ovarian follicles, were marked by alkaline phosphatase and lanthanum nitrate (LN). Active ovaries from nurse workers and physogastric queens, as well as inactive ovaries of virgin queens, were examined by transmission electron microscopy. The LN permitted better visualization of the routes of exchanges between the organs and the hemolymph. Both methods demonstrate the apparent differences between the phases of the ovary and the bee caste. In inactive ovaries of the virgin queens, the routes from the follicular epithelium to the oocyte remain closed; conversely, they are open in active ovaries of the nurse workers and physogastric queens. The differences between the methods and classes of bees are discussed. © The Author 2013. Published by Oxford University Press [on behalf of The Japanese Society of Microscopy]. All rights reserved.
Keywords: alkaline phosphatase; fat body; lanthanum nitrate; ovaries; stingless bees; vitellogenin